How to save money in a foundry production with opportunities offered by Industry 4.0 and ISO9001:2015 Standard. - Rajesh Ransing (Plenary Lecture, Jubilee 25th International Scientific and Technical Conference "Foundry production and metallurgy”, 2017)
The clauses 6.1 (risk based thinking) and 9.3 (management review) of the quality standard ISO9001:2015 and Industry 4.0 expectations are set to become one of the most important driving factors to trigger a necessary cultural change in making foundries as data driven companies. The paper discusses a practical case study on how foundries can embed risk based thinking and advanced in-process data analytics to discover opportunities for improvement across foundry operations. The paper introduces concepts such as ‘risks’, ‘uncertainty’ and ‘deficiency of knowledge’ as used in the ISO9001:2015 quality standard and relates it to the expectations on data analysis in the VDA6.3 quality standard. It introduces 7Epsilon steps that take a system approach for in-process data analysis and organizational knowledge management in ISO9001:2015 context. A novel penalty matrix based data visualization technique has been explained and the association of penalty values with risk based thinking highlighted.An example of reducing the rework effort to minimize the effect of inclusion defects in the manufacture of steel castings is discussed. The paper also introduces a simple but useful technique for quantifying qualitative factors such as quality of pouring stream, continuous/interrupted pouring etc. The paper focuses on the saving opportunities foundries can realise with data driven decision making methods and explains how the proposed methodology has ability to generate new hypotheses for achieving continual process improvement and innovation.